Изучение использования каталогов читателями - Кастанаускайте, Дануте (Knygotyra, 1987)
General conclusions, obtained during the research which was carried out at the Scientific Library of the Vilnius V. Kapsukas University in the 1970s, are presented in this article. Three phases of the research – the stock-taking of catalogs, the checking up of call slips and the analysis of questionnaires – are described. The research corroborated the idea that 70 to 80 percent of all readers consult catalogs. However, only very few of them make use of all the components of catalog system; for example, lecturers consult three to four catalogs of the nine available; students, as few as one to two catalogs. The alphabetical and alphabetical-classed catalogs of the library, as well as the general file, are most frequently consulted by readers. Among the requirements for the condition of catalogs were the following: 1) to give full information about the composition of holdings; 2) to give precise and up-to-date information on the bibliography of a particular subject, topic or problem; 3) to give wider information on the contents of a publication as well as on its form, etc. The following conclusions were drawn: 1) the main function of catalogs continues to be the information about the publication’s place in a storage unit; 2) catalogs and general files satisfy the needs, primarily, of the readers with humanitarian interests; 3) when improving catalogs and card indexes, psychological factors of information retrieval should be taken into consideration, and educational as well as ideological role of the catalogs should be increased. Using a uniform methods system, further research into the condition of catalogs should be undertaken on a complex basis.